Institutional Transformation and Islamic Mortgage Financing: Evidence from BTN Syariah and BSN - Lailatul Sa’diyah; Nabila Adenina Zidni Maulida (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2026)
Abstract The transformation of Islamic banking institutions through the spin-off policy has encouraged the development of Islamic home financing products in Indonesia. This study aims to analyze the implementation of murabahah and ijarah muntahiyah bi tamlik (IMBT) contracts after the institutional transformation of BTN Syariah into Bank Syariah Nasional (BSN). This research employed a qualitative case study approach using interviews, observations, and documentation techniques. The findings reveal that the transformation did not replace murabahah as the primary financing scheme but encouraged the adoption of more flexible financing mechanisms through IMBT contracts. In addition, the transformation strengthened governance systems, operational standardization, risk management, and sharia supervision in Islamic mortgage financing practices. The implementation of IMBT also provided greater flexibility in ownership transfer mechanisms and improved financing transparency. These findings indicate that institutional transformation contributes to strengthening sharia compliance, operational professionalism, and the competitiveness of Islamic banking institutions. This study contributes to the literature on institutional transformation and the development of Islamic mortgage financing in Indonesia